Skeletal evidence for variable patterns of handedness in chimpanzees, human hunter–gatherers, and recent British populations. (29th April 2013) - Stock, Jay T.; Shirley, Meghan K.; Sarringhaus, Lauren A.; Davies, Tom G.; Shaw, Colin N.
<x xml:space="preserve">Abstract</x> Previous studies have shown a strong correspondence between long bone bilateral asymmetry and reported handedness. Here, we compare the pattern of asymmetry in mechanical properties of the humerus and second metacarpal of Pan troglodytes, recent British industrial and medieval populations, and a broad range of human hunter–gatherers, to test whether technological variation corresponds with lateralization in bone function. The results suggest that P. troglodytes are left‐lateralized in the morphology of the humerus and right‐lateralized in the second metacarpal, while all human populations are predominantly right‐biased in the morphology of these bones. Among human populations, the second metacarpals of 63% of hunter–gatherers show right‐hand bias, a frequency similar to that found among chimpanzees. In contrast, the medieval and recent British populations show over 80% right‐lateralization in the second metacarpal. The proportion of individuals displaying right‐directional asymmetry is less than the expected 90% among all human groups. The variation observed suggests that the human pattern of right‐biased asymmetry developed in a mosaic manner throughout human history, perhaps in response to technological development.